Pembuatan Lateks Dadih dengan Proses Sentrifugasi Putaran Rendah dan Kualitas Barang Jadi Karetnya - Dadi R. Maspanger (agriTECH, 2007)
Latex from rubber tree is commercialized in the form of concentrated latex containing dry rubber of 55-60% w/w. Con- centrated latex could be produced from field latex either by high speed centrifugation, 9000-15000 rpm or skimming process. Creamed latex is concentrated latex, prepared by using creaming agents i.e. CMC and alginate, in a batch tank for 14-21 days maturation to achieve a well separation between serums and latex phase. The rate of creaming process is very slow, thereby  requiring lot of time, causing concentrated latex production by creaming technique is not popular for industries. In another side, a high speed centrifugation technique needs a high invested cost for equipments. Until now small-medium scale industries still have difficulty to produce concentrated latex by high speed centrifugation machine. The objectives of this research were to study the combination of creaming and centrifugation process, to in- crease the creaming rate by using a low speed centrifuge equipment. The result showed that treatment of field latex with addition of CMC 0,15%, maturation time 36-60 hours and centrifugation speed at 2000-2500 rpm, yielded creamed latex with its quality comparable to that produced by conventional method. This preliminary research result is expected to give useful information for further development in using of low speed centrifugation technique for creamed latex production at commercial scale. Since the equipment price of low speed centrifugation technique is cheaper than that of high speed centrifugation, this  technique is prospective to be applied at small-medium scale industries.ABSTRAKLateks dari pohon karet diperdagangkan dalam bentuk lateks pekat yang mengandung kadar karet 55-60%. Untuk memproduksi lateks pekat dapat ditempuh secara sentrifugasi pada kecepatan tinggi, 9000-15000 rpm, atau secara pendadihan. Lateks dadih merupakan lateks pekat yang dibuat dengan menggunakan bahan pendadih seperti CMC dan alginat, di dalam sebuah bejana yang didiamkan (batch) selama 14-21 hari agar terjadi pemisahan yang sempurna antara fase serum dan lateks. Pengolahan lateks dadih memerlukan waktu lama, menyebabkan hingga kini pembuatan lateks pekat secara pendadihan kurang diminati oleh kalangan industri. Penelitian ini dilaksanakan untuk mempelajari kombinasi proses sentrifugasi dan pendadihan, bertujuan mempersingkat waktu pendadihan dengan menggunakan alat sentrifugator yang dioperasikan pada putaran rendah. Hasil percobaan menunjukkan bahwa dengan pemakaian CMC sebanyak 0,15%, maturasi 36-60 jam, dan sentrifugasi 2000-2500 rpm, dapat dihasilkan lateks dadih dan barang jadi lateksnya yang bermutu  setara dengan yang dihasilkan dari lateks dadih konvensional 14 hari. Hasil penelitian ini berpotensi untuk dikembangkan ke tahap komersial, karena selain dapat memproduksi lateks dadih dalam waktu relatip singkat, juga alat dan mesin yang digunakannya cukup murah, sehingga berpotensi digunakan oleh kalangan industri kecil menengah.